2022
DOI: 10.3389/fbioe.2022.1067467
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the precursor supply for an enhanced FK506 production in Streptomyces tsukubaensis

Abstract: Tacrolimus (FK506) is a macrolide widely used as immunosuppressant to prevent transplant rejection. Synthetic production of FK506 is not efficient and costly, whereas the biosynthesis of FK506 is complex and the level produced by the wild type strain, Streptomyces tsukubaensis, is very low. We therefore engineered FK506 biosynthesis and the supply of the precursor L-lysine to generate strains with improved FK506 yield. To increase FK506 production, first the intracellular supply of the essential precursor lysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…While overexpression of the aborycin BGC genes in HNS1451 did not lead to high aborycin production, we suspect that the supply of amino acids, especially noncanonical amino acids, might be a limiting factor. This aligns with the study by Schulz et al [ 28 ], who demonstrated a significant increase in FK506 production by optimizing pipecolate supply in S. tsukubaensis . Similarly, optimizing the noncanonical amino acid synthesis pathway in HNS1451 could potentially unlock further improvements in aborycin production.…”
Section: Discussionsupporting
confidence: 92%
“…While overexpression of the aborycin BGC genes in HNS1451 did not lead to high aborycin production, we suspect that the supply of amino acids, especially noncanonical amino acids, might be a limiting factor. This aligns with the study by Schulz et al [ 28 ], who demonstrated a significant increase in FK506 production by optimizing pipecolate supply in S. tsukubaensis . Similarly, optimizing the noncanonical amino acid synthesis pathway in HNS1451 could potentially unlock further improvements in aborycin production.…”
Section: Discussionsupporting
confidence: 92%
“…It had already been shown for all producers that the overexpression of the respective lysine cyclodeaminase genes resulted in an increase in the desired secondary metabolites. A positive correlation between increased lysine availability and increased secondary metabolite production was shown in cephamycin biosynthesis in S. clavuligerus [134] and tacrolimus (SK-506) biosynthesis in S. tsukubaensis [56] (Table 3).…”
Section: Influence Of Amino Acids On Antibiotic Production In Strepto...mentioning
confidence: 93%
“…One possibility is to induce BGC expression in a native Streptomyces host. An example of the application of this strategy is the titer optimization of KF-506 in S. tsukubaensis [56]. The advantage of this strategy is that such a host is genetically tractable and genetic manipulations of the host genome are possible, including the overexpression of regulatory genes and removal of competitive pathways with gene cluster knock-out, deactivation of negative regulatory genes, and replacement of native promoters with stronger promoters.…”
Section: Bioinformatics-based Approaches For Natural Product Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of efforts have been reported for optimization of the biotechnological process of FK-506/FK-520 fermentation in S. tsukubaensis by employing different strategies including genetic approaches, strain improvement, media supplementation, metabolic and protein engineering, as well as combinational strategies (Xia et al 2013 ; Ban et al 2016 ; Wu et al 2021b ). Recently, a new optimization strategy has been presented that combines the enhancement of the precursor supply for L-lysine with the improvement of pipecolic acid formation in S. tsukubaensis (Schulz et al 2022 ). But the aspect of increasing the FK-506 yield by manipulation of regulatory steps at a global level remained uninvestigated, although the effects of phosphate and N-acetylglucosamine for FK-506 biosynthesis have been studied previously (Martín 2004 ; Martínez-Castro et al 2013 ; Ordóñez-Robles et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%